ChemInform Abstract: Regio‐ and Enantioselective Catalytic Monoepoxidation of Conjugated Dienes: Synthesis of Chiral Allylic cis‐Epoxides. Issue 28 (July 2015) - Jat, Jawahar L.; De, Saroj Ranjan; Kumar, Ganesh; Adebesin, Adeniyi Michael; Gandham, Shyam K.; Falck, John R.
Abstract A new catalyst Ti(IV)‐salan system efficiently promotes the diastereo‐ and enantioselective monoepoxidation of conjugated dienes using H2O2 even in the presence of other olefins and adjacent stereocenters.